The garment industry in low-income countries : an entry point of industrialization - Fukunishi, Takahiro; Yamagata, Tatsufumi; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book explores the means through which the garment industry contributes to industrialization, poverty reduction, empowerment of undereducated workers, in particular female laborers, and shared growth in contemporary low-income countries.
Keywords: Science